Exploring Adaptive Acoustics for Educational Spaces - Ritika Biswas; Gurmeet Prajapati (International Journal of Architectural Design and Planning, 2024)
Acoustics play a major role in educational buildings as these have high density, occupying classrooms, lecture halls, conference rooms, auditoriums, etc., engaged by students for several activities. Due to their multi-functional nature, architectural studios in particular require larger spaces and these often accommodate furnishing such as drafting board/table, screens and podium. The considerable volume of these studios can lead to compromised acoustical comfort, which may result in issues like echoes and background noise. Planning and executing these spaces are a challenge and there is always a scope for acoustical personalization for the enhanced experience of the user. This paper presents the acoustic personalisation of educational spaces aiming to explore the spatial influence on acoustic and identifying methods that would alter acoustics to user preference and needs. The acoustic personalization of existing building can be done through adaptive technologies and relevant materials. The aim is to understand the potential of adaptive acoustics in educational environments and their impact on students' psychological well-being and learning abilities. The data collection method for this research paper involves the case study of architectural department, at DIT University, accompanied by structured surveys with students of different years. The acoustically relevant data such as psychological states before and after entering the space, the impact of background noise, opinions on potential improvement like sound absorbing material, and overall acoustical comfort is gathered for examining the effects of noise on concentration and learning. This analysis helps to prepare a set of guidelines that should cater to common acoustical problems and recommendations for the process of acoustic personalization in educational space, such as designated quiet zones.
Keywords: Personalised soundscape; adaptive acoustics; educational spaces, acoustical technologies, educational buildings